2016
DOI: 10.21037/jtd.2016.05.79
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the pulmonary artery to ascending aortic ratio in patients with relatively mild chronic obstructive pulmonary disease

Abstract: The PA-A ratio evaluated by CT imaging was independently correlated with a representative pulmonary function factor (FEV1) in patients with relatively mild COPD. The results suggest that the PA-A ratio may be an important biomarker for clinical outcome in patients with mild COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The design of this cohort had been previously described in detail. 17 , 18 All enrolled patients were evaluated by medical interview, physical examination, spirometry, laboratory tests, and CT scan. COPD was defined as a postbronchodilator ratio of forced expiratory volume in 1 second (FEV 1 )/forced vital capacity (FVC) of <0.7.…”
Section: Methodsmentioning
confidence: 99%
“…The design of this cohort had been previously described in detail. 17 , 18 All enrolled patients were evaluated by medical interview, physical examination, spirometry, laboratory tests, and CT scan. COPD was defined as a postbronchodilator ratio of forced expiratory volume in 1 second (FEV 1 )/forced vital capacity (FVC) of <0.7.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the emphysema index (EI; the percentage of low attenuation area ≤ 950 Hounsfield units (HU, %LAA −950HU )) and mean wall area percentage ((WA%) of two segmental bronchi) using an in-house software program developed by the Korean obstructive lung disease study group. 18 20 …”
Section: Methodsmentioning
confidence: 99%
“…Approximately 66 % of subjects with COPD have some degree of pulmonary hypertension, and a pulmonary artery-to-ascending-aorta ratio > 1 was associated with acute exacerbation (AE) and mortality in patients with COPD [20][21][22]. Our previous study showed that the pulmonary arteryto-ascending aorta ratio was correlated with FEV 1 in patients with mild to moderate COPD [23]. In addition, a study using CT and cardiac magnetic resonance imaging reported that pulmonary artery enlargement is associated with the loss of blood volume in the distal pulmonary vessels in patients with COPD [24].…”
Section: Discussionmentioning
confidence: 97%